Basic documents pertaining to human rights in the Inter-American System (updated to September 30, 2014) (IACHR Washington, D.C.US, 2014)
Presents information on the historical background and evolution of the regional system for the protection and promotion of human rights; a brief explanation of the leading Inter-American principles in this area; and an outline that describes the establishment and evolution of the Commission and the Court, as well as an explantion of the functions and composition of those organs. Includes the texts of human rights treaties and conventions.
Keywords: HUMAN RIGHTS